An oblate spheroidal model for multi-frequency acoustic back-scattering of frazil ice - Kungl, Ákos Ferenc (Cold regions science and technology, 2020)
Frazil ice plays an important role in the growth of sea ice in the polar oceans. However, measurement of the size distribution of frazil crystals, and their number density, is still a challenging task. Most quantitative observations use acoustic back-scattering complemented with the equivalent sphere assumption. We provide a more realistic theoretical model of small frazil ice crystals by considering the scattering from an oblate spheroid, using properties appropriate for ice in the ocean. We show an alternative method to analyse measurement data, evaluating the numerical implementation against a dataset collected in October 2012 in McMurdo Sound, Antarctica. Our approach is consistent with previous laboratory studies and studies of frazil ice in rivers.
Gesehen am 21.09.2020